Pengaruh Permainan Ultaco terhadap Kemampuan Mengenal Protokol Kesehatan COVID-19 Anak RA - Setyowahyudi, Rendy; Fadlillah, M; Rahmawati, Ida Yeni; Suhendar, Uki (THUFULA, 2021)
This research aimed to know whether there was an effect of ultaco games on Group B children in understanding the covid-19 health protocol at RA Aisyiyah in Siman district Ponorogo regency. Due to the spread of the covid-19 outbreak, which infects early childhood, introducing the health protocol to prevent the infection of the virus is needed. One of the attempts is by using ultaco games or snake-ladder games. This research used a quasi-experimental method with a non-equivalent control group design. The sample was selected by using a simple random sampling. The data were analyzed using t-test, specifically a paired t-test and an independent sample t-test. Before analyzing the data, normality and homogeneity tests were carried out. The results obtained from this study are that there is an influence of the Ultaco game as a new educational game tool for early childhood on the ability to recognize the Covid-19 health protocol in group B children as indicated by the sig 2 tailed value obtained, which is 0.000 less than 0.05.